Studi perbandingan perilaku lelah AISI 316L dengan menggunakan metode eksperimen dan simulasi - Fakhriza Fakhriza; Syifaul Huzni; Murtadhahadi Murtadhahadi; Abubakar Dabet (Politeknik Negeri Lhokseumawe, 2021)
Fatigue failure occurring at a material in the dynamic loads is very dangerous because it is happen without initial guidance, fatigue testing to predict the life of use need to be done. This study focused on AISI 316L stainless steel which is used in industries because it’s mechanical properties, weldability, corrosion resistance and good machining. Fatigue testing are based on ASTM E466 and E468 standard in laboratory’s environmental by using fatigue testing machine rotary bending type. The results of fatigue testing present in S-N curve, it showed that the endurance limit of stress 277 MPa at 2870667 cycles. For comparison, from the simulasi carried out, the stress is 258 MPa at 2870667 cycles. In terms fatigue life, the material is categorized in the high cycles and fracture pattern is low stress